Impaired savings despite intact initial learning of motor adaptation in Parkinson's disease - Leow, L.; Loftus, Andrea; Hammond, G. (Springer-Verlag, 2012)
In motor adaptation, the occurrence of savings (faster relearning of a previously learned motor adaptation task) has been explained in terms of operant reinforcement learning (Huang et al. in Neuron 70(4):787–801, 2011), which is thought to associate an adapted motor command with outcome success during repeated execution of the adapted movement. There is some evidence for deficient savings in Parkinson’s Disease (PD), which might result from deficient operant reinforcement processes. However, this evidence is compromised by limited adaptation training during initial learning and by multi-target adaptation, which reduces the number of reinforced movement repetitions for each target. Here, we examined savings in PD patients and controls following overlearning with a single target. PD patients showed less savings than controls after successive adaptation and deadaptation blocks within the same test session, as well as less savings across test sessions separated by a 24-h delay. It is argued that impaired blunted dopaminergic signals in PD impairs the modulation of dopaminergic signals to the motor cortex in response to rewarding motor outcomes, thus impairing the association of the adapted motor command with rewarding motor outcomes. Consequently, the previously adapted motor command is not preferentially selected during relearning, and savings is impaired.